In vitro effect of triamcinolone and platelet-rich plasma on cytokine levels of elbow lateral epicondylitis-derived cells - de Melo Viveiros, Márcio Eduardo [UNESP]; Viveiros, Magda Massae Hata [UNESP]; da Silva, Márcia Guimarães [UNESP]; Rainho, Cláudia Aparecida [UNESP]; Schellini, Silvana Artioli [UNESP] (Springer Nature, 2022)
Background: The pathogenesis and treatment of lateral elbow epicondylitis (LEE) are still controversial. The purpose of the current study was to evaluate the production of inflammatory cytokines by LEE-derived cells and to compare the anti-inflammatory effect of triamcinolone acetonide with platelet-rich plasma (PRP) on cytokines production in primary culture of these cells. Methods: Third passage cells from primary cultures of LEE were assessed for the production of the cytokines IL-1β, IL-6, IL-8, IL-10 and TNF-α by immune-enzymatic assay (ELISA), after the treatment with 1, 10 and 100 μM triamcinolone compared to no treated controls at the time points 6, 12, 18, 24, 48, 72 and 96 h, and to PRP at 48, 72 and 96 h. Results: The cytokines IL-6 and IL-8 were produced in high concentrations by LEE cells. One, 10 and 100 μM triamcinolone induced significant decrease in the production of IL-6 and IL-8 at 48, 72 and 96 h, adding the time point 12 h for IL-8. Compared to controls, PRP caused a significant increase in the production of IL-6 and IL-8 and there was a significant increase in IL-10 production with the use of 100 μM triamcinolone at 48 h. The production of IL1-β and TNF-α was very low and did not change when the cultures were treated with triamcinolone or PRP. Conclusion: LEE-derived cells produce IL-6 and IL-8, confirming the inflammatory nature of this condition. While triamcinolone inhibited the production of IL-6 and IL-8 by LEE cells, PRP induced an increase in these cytokines compared with controls.
Keywords: Cytokines; Inflammation; Lateral elbow epicondylitis; PRP; Triamcinolone